Language and Perception - Erna Dwinata (STKIP PGRI Tulungagung, 2018)
There are several factors that underlie language choice. Factors that are often discuss by the linguist is sociology factor. This article assumes that there is a factor that are also very influential in the choice of language. Perception is one of the reason why people choose the language or change the language. This article presents a concept where language and mind collaborate. This work provides a short explaination of a fundamental cognitive process of the brain and the effect created. This work demontrates that the choices of human language is the effect of human perception. This perception is going to be a consideration for someone when he should utter low or high intonation,Â choice appropriate language level, or replace his dictions. Understanding how language can change as the effect of human perception is important in linguistics. Therefore this aricle explore how a person interprets and responds based on his perception throught the language.